Characteristics of Enzyme-Based Hydrogen Fuel Cells Using an Oxygen-Tolerant Hydrogenase as the Anodic Catalyst - Wait, A; Parkin, A; Morley, G; dos Santos, L; Armstrong, F (2010)
The special properties of O 2-tolerant [NiFe]-hydrogenases make it possible, in principle, to operate all-enzyme hydrogen fuel cells. These devices show unusual power characteristics, as revealed in a series of experiments in which the O 2-tolerant hydrogenase (Hyd-1) from Escherichia coli is used as H 2-oxidation catalyst (anode) and a bilirubin oxidase is used as O 2-reduction catalyst (cathode). In a fuel cell adaptable for variable fuel and oxidant supply, three limiting conditions were examined: (1) the anode and cathode separated by a Nafion membrane and 100% H 2 and 100% O 2 fed to the separate compartments, (2) a membrane-free mixed feed cell with a fuel-rich (96% H 2) hydrogen/oxygen mixture, and (3) a membrane-free mixed feed cell with a fuel-weak (4% H 2) hydrogen/air mixture. Condition (1) exposes the effect of O 2-crossover which is evident even for an O 2-tolerant hydrogenase, whereas condition (2) is limited by bilirubin oxidase activity on the cathode. Condition (3) yields power only under high-load (resistance) conditions that maintain a high output voltage; a low load collapses the power (akin to a circuit breaker) because of complete inactivation of the [NiFe]-hydrogenase when subjected to O 2 at high potential. Recovery of the hydrogen-poor fuel cell is not achieved simply by restoring the high load but by briefly connecting a second anode containing active hydrogenase which discharges electrons to provide a jump start. The second anode had remained active despite being in the same O 2 environment because it was not electrochemically connected to an oxidizing source (the cathode), thus demonstrating that, under 4% H 2, the presence of 20% O 2 does not, alone, cause hydrogenase inactivation, but simultaneous connection to an oxidizing potential is also required. The investigation helps to illuminate obstacles to the application of hydrogenases in fuel-cell technology and suggests phenomena that might be relevant for biology where biological membranes are engaged in H 2 oxidation under aerobic conditions. © 2010 American Chemical Society.